Romanticising knowledge and being: the epistemological and ontological formation of students through SULAM in service to society - Mohd Isnani, Zaidatulhusna; Wan Ghani, Wan Aryati; Mohd Rick, Abd Malik; Noradzan, Haslinda (Universiti Teknologi MARA, Negeri Sembilan, 2025)
SULAM (Service-Learning Malaysia, University for Society), introduced under the Malaysia Education Blueprint for Higher Education (2016), integrates classroom learning with community service to turn knowledge into action. At UiTM, SULAM is applied across courses to promote lifelong learning, allowing students to develop knowledge, soft skills, and social awareness while contributing to society. For example, in the Talent Acquisition course (HRM552), students applied career planning and job search strategies in real community settings, making learning practical, meaningful, and relevant.